Wybrane cechy realizacji adaptatorów w narracji dzieci i dorosłych - Jarmołowicz-Nowikow, Ewa (Investigationes Linguisticae, 2019)
The aim of the paper is to describe selected features of nonverbal behaviors defined as adaptors during cartoon narration by children and adults. Ten nine-year-old children and ten adults took part in the study. The results of the analysis of the material showed that: 1. children used more adaptors than adults, 2. the average time confessed to the production of adaptors by children was longer than by adults, 3. children more often than adults produced two co-occurring adaptors of different types.